Defining the Value of Personal Branding: A Framework for Quantifying Personal Brand Equity - Szántó, Péter (Marketing & Menedzsment, 2025)
THE AIM OF THE PAPER This study aims to explore the measurement of Personal Brand Equity (PBE), conceptualized as the value derived from strategic self-presentation in professional contexts. Despite increasing academic interest in Personal Branding, a standardized measurement framework remains underdeveloped. Existing research primarily focuses on branding strategies rather than quantifying the tangible benefits. Building upon Gorbatov et al.'s (2020) three-dimensional model, this study refines the concept by introducing a distinction between self-PBE (sPBE) and external-PBE (ePBE), addressing a critical gap in the literature. METHODOLOGY Using a mixed-methods approach, integrating qualitative interviews and quantitative surveys construct a comprehensive measurement model. The findings help close the research gap by revealing how Personal Branding efforts can generate measurable equity that influences career progression, professional reputation, and business success. By delineating the self-perceived and external (other-perceived) dimensions of PBE, the study provides an understanding of how individuals can strategically cultivate and leverage their personal brands for professional growth. MOST IMPORTANT RESULTS In terms of results, the research offers both theoretical and practical contributions. Theoretically, it enhances the conceptual foundation of PBE by establishing a structured framework for measurement. Practically, it equips professionals and organizations with a validated tool to assess and optimize PBE. The proposed model has implications for various domains, including career management and corporate branding. RECOMMENDATIONS By bridging the gap between Personal Branding and quantifiable equity, this study underscores the strategic significance of PBE as an asset in contemporary business environments. It provides a novel perspective on the role of Personal Branding in career sustainability from both individual and organizational perspectives, positioning PBE as a crucial element of competitive advantage in today’s dynamic labor market.